Efectos de la deshidratación y rehidratación sobre la farmacocinética de la norfloxacina en terneros - Ambros, L.A. (2006)
The purpose of this study was to evaluate the effects of dehydration and rehydration on norfloxacin pharmacokinetics after a single dose (10 mg/kg) administration to calves by the intravenous and oral routes. Of the 23 animals used in this study, 12 were dehydrated by deprivation of milk-replacer and water for 26 h before drug administration, achieving a mean dehydration percentage of 9.12 of the body weight. At 3.5 h after drug administration, all animals received milk?replacer. The pharmacokinetic profile of norfloxacin after its intravenous administration showed significant differences for the central compartment volume. After oral administration, drug absorption in the dehydrated calves showed important variations, being more rapid but significantly less than in healthy animals. Our results indicate that oral administration of 10 mg/kg every 24 h would be effective for treating bacteria with MICs up to 0.2 ?g/ml in healthy calves, however, this same treatment would be effective only for bacteria with MICs up to 0.09 ?g/ml when administered to dehydrated calves.